2008
DOI: 10.1095/biolreprod.107.064246
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dimorphic Expression of Genes in Gonads During Early Differentiation of a Teleost Fish, the Nile Tilapia Oreochromis niloticus1

Abstract: The Nile tilapia, a gonochoristic teleost fish with an XX/XY sex-determining system, provides an excellent model for studying gonadal sex differentiation because genetic all-females and all-males are available. In this study, we used quantitative real-time RT-PCR to determine the precise timing of the gonadal expression of 17 genes thought to be associated with gonadal sex differentiation in vertebrates. Gonads were isolated from all-female and all-male tilapia before (5-15 days after hatching [dah]) and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
312
2
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 373 publications
(354 citation statements)
references
References 44 publications
32
312
2
8
Order By: Relevance
“…Multiple forms of dmrt1 exist in developing testis but not in developing ovary of catfish. Male-specific expression of Dmrt1 was noticed in some species like human (Moniot et al 2000), chicken (Nanda et al 1999), frog (Osawa et al 2005), garden lizard (Sreenivasulu et al 2002) and some fish species (Fernandino et al 2006, Ijiri et al 2008, Xia et al 2007. In our study, we observed male-specific expression of multiple dmrt1s in developing and adult catfish.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Multiple forms of dmrt1 exist in developing testis but not in developing ovary of catfish. Male-specific expression of Dmrt1 was noticed in some species like human (Moniot et al 2000), chicken (Nanda et al 1999), frog (Osawa et al 2005), garden lizard (Sreenivasulu et al 2002) and some fish species (Fernandino et al 2006, Ijiri et al 2008, Xia et al 2007. In our study, we observed male-specific expression of multiple dmrt1s in developing and adult catfish.…”
Section: Discussionsupporting
confidence: 66%
“…On the contrary, dimorphic expression pattern of male and female sexspecific genes were observed in completely developed testis and ovary. Such dimorphic expression pattern was also reported during gonadal sex differentiation and/ or hormone-induced sex reversal (Alam et al 2008, Ijiri et al 2008. By contrast, in rainbow trout oestrogen treatment up-regulates female specific genes but does not suppress all male specific genes during male-to-female gonadal trans-differentiation (Vizziano-Cantonnet et al 2008).…”
Section: Discussionsupporting
confidence: 58%
“…DMRT1 has been cloned in several vertebrates and its involvement in testicular differentiation was investigated extensively (Ferguson-Smith 2007;Ijiri et al 2008;Raymond et al 2000). However, the precise role of DMRT1 during spermatogenesis remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A very close relation between foxl2 and cyp19a1a in tilapia showed the important roles of Foxl2 in regulating cyp191a and ovarian development (Ijiri et al, 2008). Fish including G. rarus have two aromatases, one is the ovarian type and one is the brain type encoded by cyp19a1a and cyp19a1b, respectively (Cao et al, unpublished;Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%